Advances in Marine Natural Product Characterisation and Separation Methodologies (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The search for bioactive marine natural products calls for the need of efficient chemical profiling strategies, together with the need to make advances in separation and characterization methodologies, in order to expedite their discovery. This Special Issue of Marine Drugs aims to highlight advances in extraction, isolation, purification and dereplication methodologies in the quest for bioactive marine natural products.